The new kid on the block : poems - Prelutsky, Jack.; Stevenson, James, 1929- (New York : Greenwillow Books, 1984)
Presents humorous poems about such strange creatures and people as Baloney Belly Billy and the Gloopy Gloopers.
Includes indexes.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
3.7
4.4
Keywords: Children's poetry, American; American poetry; Humorous poetry; American poetry; Humorous poetry